2023
DOI: 10.1155/2023/1066547
|View full text |Cite
|
Sign up to set email alerts
|

An IoMT‐Based Approach for Real‐Time Monitoring Using Wearable Neuro‐Sensors

Abstract: The Internet of Things (IoT) has demonstrated over the past few decades to be a powerful tool for connecting various medical equipment with in-built sensors and healthcare professionals to deliver superior health services that also reach remote areas. In addition to reducing healthcare costs, increasing access to clinical services, and enhancing operational effectiveness in the healthcare industry, it has also enhanced patient health safety. Recent research has focused on using EEG to assist and comprehend bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…This comparison is tabulated in Table 1 as follows, The comparison of the models based on accuracy is shown in Figure 7. Based on both figures, it can be observed that MAC TM [28], CA CNN [17], ResNet [2], MDACNN [25], RL PCIC [21], TENG ANN [16], QASDS [19], and BCNN [26] have better accuracy. Thus, they can be used for applications that require high accuracy.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This comparison is tabulated in Table 1 as follows, The comparison of the models based on accuracy is shown in Figure 7. Based on both figures, it can be observed that MAC TM [28], CA CNN [17], ResNet [2], MDACNN [25], RL PCIC [21], TENG ANN [16], QASDS [19], and BCNN [26] have better accuracy. Thus, they can be used for applications that require high accuracy.…”
Section: Discussionmentioning
confidence: 93%
“…These models must be validated for context-specific application simulations, which will assist in deploying them for different HMSM use cases. Res Net [2] 7.6 HBO LSSVM [3] 7.6 CFT [4] 5.5 AGHO [5] 6.1 SECM CA [6] 6.1 LR CoVID [7] 7.9 BHM [8] 6.3 CNN FL CoVID [9] 8.0 LAC LS-IoT [10] 6.3 NB ECG [11] 8.9 FMCW RF [12] 7.3 1D CNN [13] 5.7 CPH [14] 6.6 CNN MQTT ECG [15] 5.8 TENG ANN [16] 6.2 CA CNN [17] 6.1 PMDL [18] 6.3 QASDS [19] 8.7 FCNN [20] 5.8 RL PCIC [21] 6.8 AP3 CNN [22] 6.3 LR and XG Boost [23] 6.5 BIoT [24] 7.2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A heterogeneous network setting to measure and validate the performance in distinct scenarios was presented in [12]. Yet another real-time monitoring system with the aid of wearable neuro sensors for analyzing brain signals was proposed in [13]. However, both works did not focus on the network lifetime aspect.…”
Section: Critical Review Of Literature and Identification Of Research...mentioning
confidence: 99%
“…1(c), including patient and environment monitoring, therapeutics, medical diagnosis, and workflow, which involves patients' surveillance, personal assistant platforms, patient and personal identification, and other activities. Some of the examples related to on-body IOMT are been discussed in the papers like [7][8]…”
Section: Introductionmentioning
confidence: 99%